Multivariate Optimization of Chloride Extraction from Commercial and Raw Diesel Oil for the Determination by Ion Chromatography - Fernández Campos, Adriana (2025)
The determination of chloride in crude oil and its derivatives is a matter of utmost importance for the petroleum industry. In this study, we developed a straightforward methodology for chloride extraction for its determination in diesel oil. The extraction was performed using deionized water, employing microwave radiation as the energy source, and the quantification of chloride in the extracts was conducted by ion chromatography. The method was optimized using a multivariate approach through a Doehlert design. The optimized variables included sample mass (between 0.25 and 1.25 g), extraction time (between 5 and 35 min), and extraction temperature (between 100 and 150 °C). Only sample mass showed a significant effect on extraction efficiency, although the temperature used in the process could not exceed 150 °C to avoid sample degradation. Under the optimized conditions (0.25 g of sample in 10.00 mL of deionized water, maintained at 125 °C for 20 min), the limits of detection and quantification of the method were 0.24 μg g–1 and 0.72 μg g–1, respectively. It was successfully applied for chloride determination in six samples of both commercial and raw diesel oil. An average recovery rate of 94 ± 10% was obtained in the recovery assays.